Pembentukan Karakter Anak Melalui Kesenian Tradisional Srandul : Kajian Semiotika Roland Barthes - Sunahrowi Sunahrowi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: Traditional art’ Srandul in Cental Java and Yogyakarta have fluctuation along whit the development of other arts. Observing Srandul condition today at least we faced with two things; Frist, the existence of this traditional art began to fade. Second,this traditional art contains values of good character. The second part is a treasure of traditional arts that should be distributed to the present generation, especially children, who almost lost his identity. There are some thing behind the above problems, among others; lact of training and the preservation of Srandul for children, a lact of by society understanding about history and the economic value of Srandul. The purpose of this study was to save the Srandul traditional art and spread the values of the characters in the generation of children, and more importantly to do with vision, mission, Semarang State University as the University of Conservation is a bridge between the university and the public. Keywords: traditional, identity, culture, and character.